Effectiveness of Protected Areas in Conserving the Highly Hunted Mammal Species as Bushmeat in Southern Benin - Djagoun, C. A. M. S; SOGBOHOSSOU, Etotépé; KASSA, DAHOGA BARTHÉLÉMY; AHOUANDJINOU, Christian; AKPONA, A. Hugues; SINSIN, Brice A. (My University, 2018)
The habitat degradation together with fragmentation and illegal hunting represent a major threat for biodiversity conservation in Lama protected areas. We used a combination of questionnaire survey with local communities for ranking the hunted mammal species as bushmeat and track surveys in gridded-cell system of 500x500 m2 (n=268) to assess at what extend the management design, the anthropogenic factors and habitat type affect the occupancy model of those mammal species. Twenty mammal species have been predominantly reported by the local inhabitants to consume bushmeat species and 5 of them have been identified as the most preferable as hunted game mammals. The selection of the preferred habitat among the swampy forest, the dense forest, the tree plantations and cropland for the prioritized game species varies between species but looks similar when grouping in different orders. Some bushmeat species were found to select the more secure habitat (natural forest); suggesting the zoning system in the Lama forest can passively protect those species. However, some species such as T. swinderianus although highly hunted showed preference to anthropogenic habitat, avoiding the well secured core zone in Lama Forest. Our findings highlighted the importance of the zoning system with different management objectives in the habitat occupancy model of the highly hunted wildlife species.
Keywords: Hunted; Wildlife; Mammal; Multiple use areas